Factual Actions on DKPP Ethical Decision Results as Objects of Examination by The State Administrative Court - Raines Wadi; Muhammad Aljabbar Putra; Tarmizi Kabalmay; Muh. Aunur Rafiq Mukhlis (Jurnal Penelitian Hukum De Jure, 2023)
The Election Organizer Ethics (DKPP)’s Decision in adjudicating Election administrator ethical disputes is final and binding. This raises a problem, that is, if the DKPP decides an ethical dispute deviates from legal provisions, then there is no way to test it. Thus, the author intends to analyze comprehensively regarding, First, the final and binding nature of the results of the election administrator ethics trial from the perspective of state administrative law. Second, determine the exact form of DKPP authority as the object of testing the authority of the State Administrative Court. This paper uses normative legal research methods and regulatory approaches. There are two conclusions. First, the DKPP decision, which has an ethical dimension, is only binding on the enforcement of the code of ethics, while the implementation of DKPP authority is non-binding and becomes the object of the Administrative Court. Second, in testing DKPP authority at the State Administrative Court, the touchstone used is the conformity of the ethics trial procedure by DKPP, without including the DKPP Ethics Decision as the object of the lawsuit. This is in accordance with the current government administration legal regime which includes Factual Actions including the exercise of DKPP authority.